Hepatitis C treatment experience in a dialysis clinic: nephrologist’s perspective - Silva, Isabella Navarro da Cruz da; Omairi, Luiza Barranco; Barbosa, Juliana Silva; Ciclini, Andre Luiz; Guerra, Vanessa Cicclini (Seven Editora, 2023)
Since its discovery in 1989, hepatitis C has been gaining relevance due to its potential to develop into chronic liver disease. It is known that its prevalence is higher in dialysis patients, increasing in accordance with the time the patient remains on treatment. The diagnosis in this population may be difficult because of the nonspecific clinical picture, which may be confused with symptoms of uremia, besides variable levels of alanine aminotransferase (ALT), added to false-negative serologies for hepatitis C virus (HCV) and low viremia. Several studies seek to identify the causes of transmission within dialysis units, and most point to breaches in infection control protocol. DOI: https://doi.org/10.56238/colleinternhealthscienv1-059